The Masorah of Biblia Hebraica Stuttgartensia: Introduction and Annotated Glossary - Kelley, Page H. (William B. Eerdmans Publishing Company, 1998)
One of the barriers involved in teaching students of Biblical Hebrew about the Masorah is the lack of introductory literature on the subject. Although a lot of information about the Masorah is available in print, most of it is in technical professional journals or encyclopedia articles. Scattered about in disparate sources, often not in English, this literature is easier to ignore than it is to incorporate into introductory Hebrew classes. As a result, most students of Biblical Hebrew complete their studies without any background on the Masorah. This volume fills this gap by providing an introduction and glossary to the Masorah of the Biblia Hebraica Stuttgartensia. Although the volume could be used by any student of the Hebrew Bible, it is specifically designed to be helpful for students who are just learning Hebrew. Thus it can serve as an important parallel text for second semester or second year Hebrew courses. The introductory chapters give an overview of the field of Masoretic studies and explain the mechanics of using the Masorah of BHS. The annotated glossary provides students with definitions and explanations for most of the terms used in BHS, including examples.